2021
DOI: 10.3390/diagnostics11081400
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Saliva RT-LAMP Workflow for Rapid Identification of COVID-19 Cases and Restraining Viral Spread

Abstract: Rapid diagnostics is pivotal to curb SARS-CoV-2 transmission, and saliva has emerged as a practical alternative to naso/oropharyngeal (NOP) specimens. We aimed to develop a direct RT-LAMP (reverse transcription loop-mediated isothermal amplification) workflow for viral detection in saliva, and to provide more information regarding its potential in curbing COVID-19 transmission. Clinical and contrived specimens were used to optimize formulations and sample processing protocols. Salivary viral load was determine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…Compared to nasopharyngeal RT-qPCR only, the RT-LAMP showed a weaker specificity and PPV, reflecting the negative individuals misclassified by NP RT-qPCR but also detected positive by salivary RT-qPCR. Further, viral load in NPS samples was weakly associated to RT-LAMP sensitivity as there was no correlation between salivary and NP RT-qPCR Ct values (Spearman correlation = 0.19), suggesting different saliva and NPS viral loads, corroborating previous works 6 , 40 .…”
Section: Discussionsupporting
confidence: 85%
“…Compared to nasopharyngeal RT-qPCR only, the RT-LAMP showed a weaker specificity and PPV, reflecting the negative individuals misclassified by NP RT-qPCR but also detected positive by salivary RT-qPCR. Further, viral load in NPS samples was weakly associated to RT-LAMP sensitivity as there was no correlation between salivary and NP RT-qPCR Ct values (Spearman correlation = 0.19), suggesting different saliva and NPS viral loads, corroborating previous works 6 , 40 .…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, in a recent study of our group [ 43 ] it was observed that, although there were no observed gender differences in viral load in nasopharyngeal samples, adult males showed a significantly higher viral load in saliva samples (verified by RT-LAMP viral testing) than adult women.…”
Section: Discussionmentioning
confidence: 71%
“…These data support the conclusion that LAMP is currently the most suitable iNAAT for SARS-CoV-2 diagnosis. With the recent demonstrations of using alternative specimens, including saliva [ 154 , 155 ], and exhaled breath samples (by a face mask-based collector) [ 156 ], RT-LAMP has been transformed to adapt better to the POC diagnostic settings.…”
Section: Isothermal Nucleic Acid Amplification Testing (Inaat) Methodsmentioning
confidence: 99%